2014
DOI: 10.1200/jco.2013.50.1049
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society Classification of Lung Adenocarcinoma in Tumor Recurrence and Patient Survival

Abstract: In lung adenocarcinoma, the IASLC/ATS/ERS classification system has significant prognostic and predictive value regarding death and recurrence. Solid-predominant adenocarcinoma was also a significant predictor in patients undergoing adjuvant chemotherapy. Prognostic and predictive information is important for stratifying patients for aggressive adjuvant chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
133
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(140 citation statements)
references
References 31 publications
7
133
0
Order By: Relevance
“…The pathologic heterogeneity index was calculated from each tumor to evaluate the degree of pathologic heterogeneity, which was confirmed to reflect the survival predictive value according to the proportion of mixed histologic subtypes that were derived from the hazard ratio (HR) of each subtype using the disease-free survival curve of a large-scale study [4]. Further details about the pathologic heterogeneity index are described in the supplement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathologic heterogeneity index was calculated from each tumor to evaluate the degree of pathologic heterogeneity, which was confirmed to reflect the survival predictive value according to the proportion of mixed histologic subtypes that were derived from the hazard ratio (HR) of each subtype using the disease-free survival curve of a large-scale study [4]. Further details about the pathologic heterogeneity index are described in the supplement.…”
Section: Methodsmentioning
confidence: 99%
“…This classification was devised to understand the histological subtypes and their histo-molecular correlations. Since the release of this classification, many studies have investigated the possible correlations among the most predominant subtypes, driver mutations and patient prognosis [4, 5]. However, prognostic stratification considering only the most predominant subtypes has shown substantial limitation due to the fact that more than 80% of invasive lung adenocarcinomas show mixed type including two or more of histologic subtypes [69].…”
Section: Introductionmentioning
confidence: 99%
“…3-21 Seventeen studies demonstrated significant differences in patient outcomes among the histologic subtypes 3-12, 14, 15, 17-21 while only 2 studies did not. 13, 16 The survival rate for predominant histological subtypes and the outcome and the distribution of each histological subtypes is outlined in Figure 3 .…”
Section: Introductionmentioning
confidence: 99%
“…They reported that MIP and SOL predominant subgroups were significantly associated with lymph node metastases at the resection site and that they were a significant association with aggressive postoperative behavior that favors early distant metastasis. 17 Zhang et al concluded in their retrospective study of 243 patients with resected NSCLC that tumor size was not a reliable predictor of the N0 status and that histologic subtyping might be useful in avoiding systematic lymph node dissection in more than one-third of small (≤ 2 cm) NSCLC. 43 In our retrospective study, we identified that the presence of MIP pattern and absence of LEP pattern was significantly associated with occult mediastinal lymph node metastasis in patients with clinically diagnosed N0/N1 lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, applying the most predominant subtype concept means that other minor yet important components may be excluded from consideration. In this context, we aimed to determine the relative prognostic significance of each subtype from a development cohort using data from a large study group [9]. Furthermore, we attempted to establish a pathologic index based on the relative prognostic significance of each subtype that accurately reflects the pathologic subtypes and overall heterogeneity of lung adenocarcinomas.…”
Section: Introductionmentioning
confidence: 99%